Lectures on the psychology of women - Chrisler, Joan C.; Golden, Carla; Rozee, Patricia D. [ (Patricia Denise)] (New York : McGraw-Hill, 2008)
Designed as a companion reader to any Psychology of Women textbook. This collection features essays by experienced teachers and leading experts in Psychology of Women. It includes lectures written in an informal manner, that speaks to students directly and addresses questions that they often ask
1. Status of women -- 2. Women's bodies -- 3. Diversity of women -- 4. Violence against women -- 5. Women's mental health
Includes bibliographical references and index
Keywords: Women -- Psychology